A Qualitative Analysis of Cross-cultural Adjustment and Job Performance in the Hotel Industry: The Case of Saudi Arabia - Alkhoraif, Abdullah (Journal of Ecohumanism, 2024)
Individual and organizational-level cross-cultural adjustments are necessary in the hospitality sector because of its diverse and dynamic teams and guests. The aim of this research is to comprehend the variables that explain how job performance is affected by cross-cultural adjustment. A qualitative study was carried out, with an emphasis on the traits of the Saudi culture and the opinions on job performance, satisfaction, and the overall environment at work. To determine how high-context and low-context cultural norms differ from one another and what effects they have on various levels, ten individuals were interviewed. Thematic analysis was used to examine the transcribed data, find patterns, and discuss the most significant relationships. The results demonstrated that a cross-cultural adjustment in a team of hotel industry in Saudi Arabia is affected due to the lack of cultural balance and inclusiveness. This may lead to communication problems and a challenging work environment, which can affect employees' engagement and job performance. The recommendations included focusing on enhancing the present recruitment procedure to develop more culturally balanced teams and evaluating the team's time-management skills, which is a factor that makes it challenging for employees to participate in activities of diverse cultures.